Therapeutic and preventive effect of the antidisbiotic agent kvertulin on the condition of the oral cavity of patients who received oral applications of fried sunflower oil - Iu. Labush (Kazimierz Wielki University, 2022)
Background. To determine the possibility of prevention of dental complications in the consumption of fried sunflower oil (FSO) with the antidisbiotic agent Kvertulin. Methods. Patients underwent oral FSO applications for 10 days. The antidisbiotic agent was taken sublingually. The condition of the oral cavity was assessed by such indicators as salivation rate, hygienic indices, level in saliva of biochemical markers of inflammatory-dystrophic (elastase, MDA, urease), dysbiotic processes (urease, lysozyme, degree of dysbiosis) and antioxidant protection (catalase, index API). Results. It was found that the consumption of FSO increases the level of elastase, urease, MDA and the degree of dysbiosis in saliva, but reduces the level of lysozyme, catalase and API index. Previous use of Kvertulin significantly reduced the level of elastase, urease, MDA and the degree of dysbiosis and increased the level of lysozyme, catalase and API index. The therapeutic and prophylactic efficacy of quertulin in the patients who consumption of FSO was 64.4 %. Conclusion: Consumption of FSO causes the development of inflammatory-dystrophic and dysbiotic complications in the oral cavity, which can be largely prevented with the antidisbiotic agent Kvertulin.